2006
DOI: 10.1002/anie.200504599
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Release of Encapsulated Materials inside Living Cells

Abstract: Escape route: The laser‐initiated release of fluorescently labeled polymers from polyelectrolyte‐multilayer microcapsules is demonstrated inside living cancer cells. A polymer is incorporated in capsules with metal nanoparticles in their walls, which serve as light‐absorbing centers. The capsules are internalized by cells and near‐infrared light ruptures the walls of the capsules, thus releasing the content into the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
295
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 493 publications
(304 citation statements)
references
References 124 publications
3
295
0
6
Order By: Relevance
“…And as the size of the particles (clusters) increases, so does the damping factor and the absorption. On the other hand, the light scattering gets weaker, as the size of particles (clusters) increases [14,15] . Thus, the metal cluster presents the dark-blue masses.…”
Section: Buds Watered With Standard Solution or Noble Metal Colloids mentioning
confidence: 99%
See 1 more Smart Citation
“…And as the size of the particles (clusters) increases, so does the damping factor and the absorption. On the other hand, the light scattering gets weaker, as the size of particles (clusters) increases [14,15] . Thus, the metal cluster presents the dark-blue masses.…”
Section: Buds Watered With Standard Solution or Noble Metal Colloids mentioning
confidence: 99%
“…3, the dark-field microscopic observation shows the roots scatter the weak light, while the metal clusters scatter stronger light. As the size of the metal clusters decreases, the surface plasmon resonance increases, as does the scattering of light [14,15]. Therefore, the particles (clusters) size on the roots are smaller than these on the leaves.…”
Section: Buds Watered With Standard Solution or Noble Metal Colloids mentioning
confidence: 99%
“…Their use in different fields such as optoelectronics, [1] catalysis, [2] diagnostics, [3] drug delivery, [4,5] etc. has stimulated scientists in different field, such as physics, chemistry, biotechnology, etc.…”
Section: Introductionmentioning
confidence: 99%
“…they dissipate heat [64][65][66]. The locally generated heat is sufficient to open the capsules and facilitate cargo release, not only from the capsule but also from the organelle [67][68][69]. Carregal-Romero et al demonstrated this upon release of a pH sensor, which monitored differences in pH of the lysosomes and the cytosol along its way [68].…”
Section: Light Acting On Plasmonic Nanoparticles As External Trigger mentioning
confidence: 99%